Medium-entropy garnet type solid electrolyte, preparation method thereof and diaphragm-free lithium ion battery

By using a variety of elements for doping in garnet-type solid electrolytes, the use of high-value elements and the ionic conductivity is improved, the problems of large use of high-value elements and high sintering temperature in the prior art are solved, and the low-temperature synthesis of materials and the improvement of economic value are achieved.

CN119920959APending Publication Date: 2025-05-02CHONGQING TALENT NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410914164.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-09
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

While improving the ionic conductivity, the existing garnet solid electrolytes have a large amount of high-value elements, resulting in high economic costs and high sintering temperatures that are not of good economic value.

Method used

By doping three or four elements at the doping site, a medium-entropy garnet-type solid electrolyte is obtained, reducing the content of high-value elements and improving ionic conductivity. The specific method is to use high-value elements with +5 valence and elements with high-value elements assimilation valence with high-value elements, and at the same time use +4 valence elements for fine-tuning of the structure to make the overall ion radius close to the hex-coordinated ion radius of Zr4+, reducing the impact on the lithium ion transmission channel.

Benefits of technology

It has achieved a reduction in the content of high-value elements and an increase in ionic conductivity, reduced production costs, is suitable for large-scale production, and reaches a balance between ionic conductivity and economic value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920959A_ABST
    Figure CN119920959A_ABST
Patent Text Reader

Abstract

The invention relates to a medium-entropy garnet type solid electrolyte, a preparation method thereof and a lithium ion battery. The general structural formula of the medium-entropy garnet type solid electrolyte is Li7-xLa3Zr2-2x (M1M2) xO12, x is greater than 0 and less than or equal to 1, M1 represents a + 5-valent element and is selected from one or two elements of Ta, Nb, V and Sb, and M2 represents a + 4-valent element and is selected from one or two elements of Ce, Sn, Hf, Mo, Ir and Pd. The medium-entropy garnet type solid electrolyte is low in content of high-value elements, the entropy value is increased through a special doping mode, and low-temperature synthesis of materials and cost reduction are facilitated. By adjusting the lithium vacancy concentration and the overall structure of the doped elements, the ionic conductivity is effectively improved, and the balance of the garnet type solid electrolyte on the ionic conductivity and the economic value is realized. The preparation method is simple and convenient to operate, low in raw material cost, low in sintering temperature and suitable for mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of diaphragm-free lithium batteries and relates to a medium-entropy garnet-type solid electrolyte and a preparation method thereof and a diaphragm-free lithium-ion battery. Background Art

[0002] Garnet-type solid electrolytes have attracted widespread attention in recent years due to their high ionic conductivity, wide electrochemical window, thermodynamic stability, and stability to lithium metal. The general structural formula of garnet-type solid electrolytes is Li 3+x A 3 B 2 O 12 , which has abundant doping sites, and different doping methods will significantly affect the ionic conductivity of garnet-type solid electrolytes.

[0003] Traditional doping methods are single or binary doping, which aims to change its crystal structure at low temperatures, or to make the dopants work synergistically to facilitate lithium ion transmission. Although single and binary doping can greatly improve ion conductivity, the doping amount of high-value elements is large, especially for the large-scale use of Ta and Ga, which leads to high economic costs. In addition, the sintering of traditional garnet requires a high temperature of about 1200°C, which does not have good economic value. Summary of the invention

[0004] Problem that the invention aims to solve

[0005] In view of the above problems, it is necessary to provide a doping method that can achieve a high level of ionic conductivity while reducing the content of high-value elements, so as to achieve a balance between ionic conductivity and economic value of garnet-type solid electrolytes.

[0006] Solutions for solving problems

[0007] In the present invention, by using three or four elements for doping at the doping site, a medium entropy garnet-type solid electrolyte is obtained, which achieves a reduction in the content of high-value elements and an improvement in ionic conductivity. Specifically, the present invention adjusts the lithium vacancy concentration of the garnet electrolyte by using a high-value element with a valence of +5 and an element with the same valence as the high-value element, and at the same time uses a +4 valence element to fine-tune the overall ionic radius in structure, so that the overall ionic radius formed by the combination of doping elements is similar to that of Zr 4+ The difference in the radius of the six-coordinate ions is small, which reduces the impact on the lithium ion transmission channel and effectively improves the ion conductivity. In addition, this doping method, in addition to reducing the content of high-value elements, is also conducive to the low-temperature synthesis of electrolyte materials due to the increase in entropy value, further reducing production costs. Ultimately, a balance between ion conductivity and economic value of garnet-type solid electrolytes is achieved.

[0008] Specifically, the present invention provides a medium entropy garnet solid electrolyte, the general structural formula of which is Li 7-x La 3 Zr 2-2x (M 1 M 2 ) x O 12 ,

[0009] Among them, 0<x≤1,

[0010] M 1 represents a +5 valence element, one or two elements selected from Ta, Nb, V, Sb,

[0011] M 2 represents a +4 valence element, one or two elements selected from Ce, Sn, Hf, Mo, Ir, Pd, M 1 and M 2 The total number of element types is 3 or 4,

[0012] M 1 With M 2 The content ratio is an equimolar ratio,

[0013] When M 1 When there are two elements, M 1 The content ratio between the two elements is an equimolar ratio.

[0014] When M 2 When there are two elements, M 2 The content ratio between the two elements is an equimolar ratio.

[0015] According to the above-described intermediate entropy garnet solid electrolyte, 0.25≤x≤1.

[0016] According to the above-mentioned intermediate entropy garnet-type solid electrolyte, wherein M 1 One or two elements selected from Ta, Nb, V, M 2 One or two elements selected from Ce, Sn, and Mo.

[0017] According to the above-mentioned intermediate entropy garnet-type solid electrolyte, wherein the M 1 For Ta and Nb, the M 2 For Ce and Sn.

[0018] Furthermore, the present invention also provides a method for preparing the intermediate entropy garnet-type solid electrolyte according to the above, which comprises the following steps:

[0019] Step S1: mixing raw materials for forming the intermediate entropy garnet-type solid electrolyte in a stoichiometric ratio and calcining to obtain a calcined powder; and

[0020] Step S2: crushing and sintering the calcined powder obtained in step S1 to obtain a medium-entropy garnet-type solid electrolyte.

[0021] According to the preparation method described above, in step S1, the raw material includes salts or oxides of various elements for the medium-entropy garnet-type solid electrolyte.

[0022] According to the above-mentioned preparation method, the amount of lithium added in the raw material is 10 mass % to 20 mass % in excess of the amount calculated by the stoichiometric ratio.

[0023] According to the above preparation method, the calcination temperature is 800-900° C. and the calcination time is 3-10 hours.

[0024] According to the preparation method described above, the sintering temperature is 1000-1150° C., and the sintering time is 3-6 hours.

[0025] In addition, the present invention also provides a separator-free lithium-ion battery, which comprises the garnet-type solid electrolyte described above or the garnet-type solid electrolyte prepared according to the preparation method described above.

[0026] Effects of the Invention

[0027] The above technical solution of the present invention has the following beneficial effects:

[0028] 1) The medium-entropy garnet-type solid electrolyte provided by the present invention has a low content of high-value elements, a low raw material cost, and an entropy value is increased through a special doping method, which is conducive to low-temperature synthesis of materials and further reduces production costs.

[0029] 2) By adjusting the lithium vacancy concentration and lithium ion concentration as well as the overall structure of the doping elements, the ionic conductivity is effectively improved, and the balance between the ionic conductivity and economic value of the garnet-type solid electrolyte is achieved.

[0030] 3) The preparation method of the medium-entropy garnet solid electrolyte provided by the present invention is simple to operate, has low raw material cost, low sintering temperature, and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The impedance spectra of Examples 1 to 4 of the present invention and Comparative Examples 1 to 2 are shown. DETAILED DESCRIPTION

[0032] The following describes the embodiments of the present invention, but the present invention is not limited thereto. The present invention is not limited to the various structures described below, and various changes can be made within the scope of the invention claim, and the embodiments obtained by appropriately combining different embodiments and appropriately combining the technical means disclosed in the embodiments are also included in the technical scope of the present invention. In addition, all the documents recorded in this specification are cited in this specification as references.

[0033] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.

[0034] In this specification, the "mesoentropy" mentioned refers to the configurational entropy value of the material being 1R to 1.5R.

[0035] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0036] In this specification, unless otherwise specified, the word "multiple" in "multiple", "multiple", "plurality", etc. means a numerical value of 2 or more.

[0037] In the present specification, the term “substantially”, “substantially” or “essentially” means that the error is less than 5%, or less than 3%, or less than 1% compared with a relevant perfect standard or theoretical standard.

[0038] In this specification, unless otherwise specified, "%" means mass percentage.

[0039] In this specification, the "normal temperature" or "room temperature" used means an indoor ambient temperature of "23±2°C".

[0040] In this specification, the meanings of “may” or “can” include both existence and non-existence, and both performing a certain process and not performing a certain process.

[0041] In the present specification, "optional" and "optionally" mean that the event or situation described below may or may not occur, and that the description includes cases where the event occurs and cases where it does not occur.

[0042] The term "comprising" and any variations thereof in the specification and claims of the present invention and the above drawings are intended to cover non-exclusive inclusions. For example, a process, method or system, product or device comprising a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.

[0043] In this specification, the references to "some / certain / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0044] <First aspect>

[0045] The first aspect of the present invention provides a medium entropy garnet solid electrolyte having a general structural formula of Li 7- x La 3 Zr 2-2x (M 1 M 2 ) x O 12 , where 0<x≤1;

[0046] M 1 represents a +5 valence element, one or two elements selected from Ta, Nb, V, Sb,

[0047] M 2 represents a +4 valence element, one or two elements selected from Ce, Sn, Hf, Mo, Ir, and Pd,

[0048] M 1 and M 2 The total number of element types is 3 or 4,

[0049] M 1 and M 2 The content ratio is an equimolar ratio,

[0050] When M 1 When there are two elements, M 1 The content ratio between the two elements is an equimolar ratio.

[0051] When M 2 When there are two elements, M 2 The content ratio between the two elements is an equimolar ratio.

[0052] In some specific embodiments, the value of x is preferably 0.25≤x≤1, such as 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, etc.

[0053] In some preferred embodiments, the M 1 M may be selected from one or two elements of Ta, Nb, and V, such as a group consisting of Ta and Nb, a group consisting of Ta and V, and a group consisting of Nb and V;2 One or two elements may be selected from Ce, Sn, and Mo, for example, a group consisting of Ce and Sn, or a group consisting of Ce and Mo.

[0054] In some more preferred embodiments, from the perspective of ionic radius, since Ta 5+ With Nb 5+ The ionic radius is closer to that of Zr 4+ The ionic radius, therefore, the M 1 selected from the group consisting of Ta and Nb; and from the perspective of stability, Mo 4+ It is easy to be oxidized to a higher valence state during the heating process. The synthesis conditions require a strict oxygen-free environment. 2 is selected from the group consisting of Ce and Sn, and further, when M 1 is selected from the group consisting of Ta and Nb and M 2 When selected from the group consisting of Ce and Sn, the M 1 With M 2 The combined overall ionic radius is similar to that of Zr 4+ The six-coordinate ion radius is very close, which is more conducive to the transmission of lithium ions.

[0055] In some more specific embodiments, the structural formula of the garnet-type solid electrolyte can be Li 7- x La 3 Zr 2-2x (Ta 0.5 Nb 0.5 Ce 0.5 Sn 0.5 ) x O 12 , 0<x≤1, preferably 0.25≤x≤1. Among them, by doping with Ta elements and Nb elements, the ion conductivity is improved, and by doping with Ce and Sn elements, the lithium ion content is adjusted on the one hand, and the ion radius is adjusted on the other hand to make the overall ion radius close to Zr 4+ The ionic radius further ensures the effective improvement of ionic conductivity. In addition, the doping elements are relatively low in price and easy to obtain.

[0056] In the present invention, considering that the common tetravalent Ti element is easily reduced to trivalent by lithium metal at low voltage (about 1.5V), and the intrinsic defect of tetravalent Ti is also exhibited in lithium aluminum titanium phosphate (LATP) and lithium lanthanum titanate (LLTO) solid electrolytes, Ti is not selected as the doping element in the present invention.

[0057] <Second Aspect>

[0058] The second aspect of the present invention provides a method for preparing the intermediate entropy garnet-type solid electrolyte described in the first aspect, comprising the following steps:

[0059] Step S1: mixing raw materials for forming the intermediate entropy garnet-type solid electrolyte in a stoichiometric ratio and calcining to obtain a calcined powder; and

[0060] Step S2: crushing and sintering the calcined powder obtained in step S1 to obtain a medium-entropy garnet-type solid electrolyte.

[0061] The raw material includes the elements included in the garnet solid electrolyte described in the first aspect, which will not be described in detail here. In some specific embodiments, the raw material can be a salt or oxide containing each element used for the medium entropy garnet solid electrolyte, and the salt can be, for example, a carbonate, an acetate, a nitrate, etc.

[0062] In some specific embodiments, since the raw materials containing lithium are very volatile at high temperatures, it is necessary to ensure that the Li participating in the reaction meets the stoichiometric ratio so that the reaction can be fully complete. Therefore, an excess of lithium source is added to compensate for the loss of lithium at high temperatures. The amount of the raw material containing lithium element added is 10% to 20% by mass on the basis of the amount calculated by the stoichiometric ratio, for example, 11% by mass, 12% by mass, 13% by mass, 14% by mass, 16% by mass, 18% by mass, etc.

[0063] In some specific embodiments, the present invention does not specifically limit the equipment used in the mixing step, and it can be a commonly used mixing device in the art, such as a ball mill, etc. In some preferred embodiments, in order to improve the uniformity of the raw materials, the material-ball ratio in the mixing step can be 1:(4-10), for example, 1:5, 1:6, 1:7, 1:8, 1:9, etc.; the mixing time can be 2-6h, for example, 3h, 4h, 5h, etc.

[0064] In some specific embodiments, the calcination temperature in step S1 is 800-900°C, for example, 820°C, 840°C, 850°C, 870°C, 890°C, etc. If the calcination temperature is too low, the cubic phase will not appear in the material, the lithium source will not be fully decomposed, and the electrolyte material will not be dense or even cracked during the secondary sintering process. If the calcination temperature is too high, the lithium source in the material will volatilize too quickly, affecting the secondary sintering and resulting in low ionic conductivity. The calcination time is 3-10h, for example, it can be 4h, 5h, 6h, 7h, 8h, 9h, etc.

[0065] In some specific embodiments, the sintering temperature in step S2 is 1000-1150°C, for example, it can be 1020°C, 1050°C, 1080°C, 1100°C, 1120°C, etc. When the sintering temperature is too low, the material will not be dense and cannot be effectively converted into a cubic structure. When the sintering temperature is too high, Li will overflow from the electrolyte surface, resulting in low conductivity. The present invention realizes low-temperature synthesis by increasing the entropy value. Compared with the sintering temperature of the traditional garnet-type solid electrolyte, the sintering temperature of the present invention is lower, which reduces the production cost. The sintering time is 3-6h, for example, it can be 3.5h, 4h, 4.5h, 5h, 5.5h, etc.

[0066] In some specific embodiments, in order to improve the density of the solid electrolyte and thus help improve its ionic conductivity, a screening step may be included after the calcination step and before the sintering step. The present invention does not specifically limit the selection of the screen, which may be selected from 50 mesh, 100 mesh, 150 mesh, 200 mesh, etc.

[0067] In some more specific embodiments, in order to facilitate the subsequent processing and use of the solid electrolyte, a tabletting step may be included after the sieving step. The pressure in the tabletting step is not particularly limited and may be 10 to 30 MPa, for example, 15 MPa, 20 MPa, 25 MPa, etc.

[0068] <Third Aspect>

[0069] The third aspect of the present invention provides a membrane-free lithium-ion battery, which comprises the intermediate-entropy garnet-type solid electrolyte according to the <first aspect> or the intermediate-entropy garnet-type solid electrolyte prepared according to the preparation method described in the <second aspect>.

[0070] Example

[0071] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0072] Example 1: x = 0.25

[0073] Garnet-type solid electrolyte Li 6.75 La 3 Zr 1.5 (Ta 0.5 Nb 0.5 Ce 0.5 Sn 0.5 )0.25 O 12 Preparation method

[0074] Accurately weigh the corresponding lithium carbonate, lanthanum oxide, zirconium oxide, tin oxide, niobium oxide, cerium oxide, and tantalum oxide according to the stoichiometric ratio (molar ratio), wherein the lithium carbonate is in excess of about 15% by mass. Use a vibrating ball mill to mix for 4 hours, with a material-ball ratio of 1:6. Place the obtained mixed powder in a muffle furnace and calcine at 850°C for 6 hours.

[0075] Then, the obtained powder was crushed, pressed into a disc with a diameter of 17 mm at 20 Mp, and then placed in a magnesium oxide crucible and sintered at 1100° C. for 4 h to obtain a solid electrolyte material.

[0076] Example 2: x=0.5

[0077] Garnet-type solid electrolyte Li 6.5 La 3 Zr(Ta 0.5 Nb 0.5 Ce 0.5 Sn 0.5 ) 0.5 O 12 Preparation method

[0078] Accurately weigh the corresponding lithium carbonate, lanthanum oxide, zirconium oxide, tin oxide, niobium oxide, cerium oxide, and tantalum oxide according to the stoichiometric ratio (molar ratio), wherein the lithium carbonate is in excess of about 15% by mass. Use a vibrating ball mill to mix for 4 hours, with a material-ball ratio of 1:6. Place the obtained mixed powder in a muffle furnace and calcine at 850°C for 6 hours.

[0079] Then, the obtained powder was crushed, pressed into a disc with a diameter of 17 mm at 20 Mp, and then placed in a magnesium oxide crucible and sintered at 1100° C. for 4 h to obtain a solid electrolyte material.

[0080] Example 3: x=0.8

[0081] Garnet-type solid electrolyte Li 6.2 La 3 Zr 0.4 (Ta 0.5 Nb 0.5 Ce 0.5 Sn 0.5 ) 0.8 O 12 Preparation method

[0082] Accurately weigh the corresponding lithium carbonate, lanthanum oxide, zirconium oxide, tin oxide, niobium oxide, cerium oxide, and tantalum oxide according to the stoichiometric ratio (molar ratio), wherein the lithium carbonate is in excess of about 15% by mass. Use a vibrating ball mill to mix for 4 hours, with a material-ball ratio of 1:6. Place the obtained mixed powder in a muffle furnace and calcine at 850°C for 6 hours.

[0083] Then, the obtained powder was crushed, pressed into a disc with a diameter of 17 mm at 20 Mp, and then placed in a magnesium oxide crucible and sintered at 1100° C. for 4 h to obtain a solid electrolyte material.

[0084] Example 4: x=1

[0085] Garnet-type solid electrolyte Li 6 La 3 (Ta 0.5 Nb 0.5 Ce 0.5 Sn 0.5 ) 12 Preparation method

[0086] Accurately weigh the corresponding lithium carbonate, lanthanum oxide, tin oxide, niobium oxide, cerium oxide, and tantalum oxide according to the stoichiometric ratio (molar ratio) of the elements, wherein the lithium carbonate is in excess of about 15% by mass. Use a vibrating ball mill to mix for 4 hours, with a material-ball ratio of 1:6. Place the obtained mixed powder in a muffle furnace and calcine at 850°C for 6 hours.

[0087] Then, the obtained powder was crushed, pressed into a disc with a diameter of 17 mm at 20 Mp, and then placed in a magnesium oxide crucible and sintered at 1100° C. for 4 h to obtain a solid electrolyte material.

[0088] Comparative Example 1: x = 0

[0089] Garnet-type solid electrolyte Li 7 La 3 Zr 2 O 12 Preparation method

[0090] According to the stoichiometric ratio (molar ratio) of Li:La:Zr of 7:3:2, the corresponding lithium carbonate, lanthanum oxide and zirconium oxide are accurately weighed, wherein the lithium carbonate is in excess of about 15% by mass. A vibrating ball mill is used to mix for 4 hours, with a material-ball ratio of 1:6. The obtained mixed powder is placed in a muffle furnace and calcined at 850°C for 6 hours.

[0091] Then, the obtained powder was crushed, pressed into a disc with a diameter of 17 mm at 20 Mp, and then placed in a magnesium oxide crucible and sintered at 1100° C. for 4 h to obtain a solid electrolyte material.

[0092] Comparative Example 2: Ta-doped LLZO

[0093] Garnet-type solid electrolyte Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 Preparation method

[0094] Accurately weigh the corresponding lithium carbonate, lanthanum oxide, zirconium oxide, and tantalum oxide according to the stoichiometric ratio (molar ratio) of the elements, wherein the lithium carbonate is in excess of about 15% by mass. Use a vibrating ball mill to mix for 4 hours, with a material-ball ratio of 1:6. Place the obtained mixed powder in a muffle furnace and calcine at 850°C for 6 hours.

[0095] Then, the obtained powder was crushed, pressed into a disc with a diameter of 17 mm at 20 Mp, and then placed in a magnesium oxide crucible and sintered at 1100° C. for 4 h to obtain a solid electrolyte material.

[0096] Performance Testing

[0097] 1. Ionic conductivity test

[0098] The surface of the obtained solid electrolyte material is polished smooth, and a silver conductive layer is sputtered on both sides of the electrolyte material using an ion sputtering device to produce a lithium ion blocking electrode.

[0099] The solid electrolyte material with the blocked electrode was placed in an electrochemical workstation for EIS testing. The ionic conductivity was calculated according to the formula σ = L / (S·R), where L is the distance between the blocking electrodes on both sides of the solid electrolyte, S is the area of ​​the blocking electrode, and R is the real value of the intersection of the oblique line representing the Warburg impedance and the semicircle representing the grain boundary response in the impedance spectrum. The test results are shown in Figure 2. Figure 1 And as shown in Table 1.

[0100] Table 1

[0101] name Impedance(Ω) Ionic conductivity (mS / cm) Example 1 256.4 0.309 Example 2 147.2 0.441 Example 3 143.9 0.284 Example 4 347.8 0.168 Comparative Example 1 6462 0.0129 Comparative Example 2 340.5 0.210

[0102] From Table 1 and Figure 1 It can be seen that the medium-entropy garnet-type solid electrolytes prepared in Examples 1 to 4 of the present invention have the characteristics of low impedance and high ionic conductivity compared with Comparative Examples 1 to 2, and the preparation method of the present invention has low raw material cost and low sintering temperature, achieving a balance between ionic conductivity and economic value of the garnet-type solid electrolyte, and is suitable for mass production.

[0103] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.

[0104] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A medium entropy garnet solid electrolyte, characterized in that: Its general structural formula is Li 7-x Ln3Z 2-2x (M1M2) x O 12 , Among them, 0<x≤1, M1 represents a +5 valence element, selected from one or two elements of Ta, Nb, V, and Sb, M2 represents a +4 valence element, one or two elements selected from Ce, Sn, Hf, Mo, Ir, and Pd, The total number of element types of M1 and M2 is 3 or 4, The content ratio of M1 and M2 is equimolar ratio. When M1 is two elements, the content ratio between the two elements of M1 is an equimolar ratio. When M2 is two elements, the content ratio between the two elements of M2 is an equimolar ratio.

2. The medium-entropy garnet solid electrolyte according to claim 1, wherein 0.25≤x≤1.

3. The medium-entropy garnet solid electrolyte according to claim 1 or 2, wherein M1 is selected from one or two elements of Ta, Nb, and V, and M2 is selected from one or two elements of Ce, Sn, and Mo. 4 . The medium-entropy garnet-type solid electrolyte according to claim 1 , wherein the M1 is Ta and Nb, and the M2 is Ce and Sn.

5. A method for preparing the medium-entropy garnet solid electrolyte according to any one of claims 1 to 4, characterized in that: It includes the following steps: Step S1: mixing raw materials for forming the intermediate entropy garnet-type solid electrolyte in a stoichiometric ratio and calcining to obtain a calcined powder; and Step S2: crushing and sintering the calcined powder obtained in step S1 to obtain a medium-entropy garnet-type solid electrolyte.

6. The preparation method according to claim 5, wherein in step S1, the raw material comprises salts or oxides of various elements used for the medium-entropy garnet-type solid electrolyte.

7. The preparation method according to claim 5 or 6, wherein the amount of lithium added to the raw material is 10 mass % to 20 mass % in excess of the amount calculated by the stoichiometric ratio.

8. The preparation method according to any one of claims 5 to 7, wherein the calcination temperature is 800 to 900°C; and the calcination time is 3 to 10 hours. 9 . The preparation method according to claim 5 , wherein the sintering temperature is 1000 to 1150° C. and the sintering time is 3 to 6 hours.

10. A separator-free lithium-ion battery, comprising the garnet-type solid electrolyte according to any one of claims 1 to 4 or the garnet-type solid electrolyte prepared by the preparation method according to any one of claims 5 to 9.